Penerapan Model Pembelajaran Kooperatif Make a Match pada Materi Sifat Bangun Ruang untuk Meningkatkan Respon dan Prestasi Belajar Siswa Kelas V SDN Penambong - Astuti, Mahyuni (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
This study aims to determine the response and increase student achievement after implementation of cooperative learning Make A Match in the subjects of Mathematics material properties of Build Space in class V SDN Penambong. This research is a classroom action research. The results of data analysis for each cycle as follows: First cycle the learning outcome with an average score of 56.17, with classical completeness amounted to 52.78%, and the average of 66 student responses to both categories are good. In the second cycle the learning outcome of students has increased, where classical completeness score of 75% with an average score of 72.03, and the average score of the students' responses also increased, 69.36 in good category either. And, the third cycle student the learning outcome has increased significantly, in which classical completeness of 94.44% with an average score of 48.88, and the average score student responses by 77 with excellent category. This indicates that students enjoy learning Mathematics after the application of learning models, in particular models of cooperative learning Make A Match. It can be concluded that the response and students Mathematics achievement has increased after the implementation of cooperative learning model of Make A Match.